Antimicrobial activity and identification of bioactive compounds of Söfö-söfö (Acmella cf) leaf extract using GC-MS - Maria bintang; Faoziduhu Bawamenewi; Mega Safithri; Fachriyan H Pasaribu (IPB University, 2016)
Söfö-söfö is a traditional medicinal plant from Nias Island that can cure fever, cough, diarrhea and fungal infections on the skin. However, the scientific basis of these plants is unknown. The aim of this research was to extract the Söfö-söfö leaf by maceration method using two solvents that were 70 % ethanol and ethyl acetate, to test the antimicrobial activity of the extract by Agar diffusion method against Staphylococcus aureus, Eschercia coli, and Candida albican, and analyze secondary metabolite compounds by fitochemistry test and to determine the components of bioactive compounds by GC-MS. The results showed that the best solvent for making Söfö-söfö extract as antimicrobial is ethyl acetate with a minimum inhibitory concentration of 4000 ppm to S. aureus (1.25 ± 0.35 mm), E. coli (1 mm) and C. albican 6000 ppm (1.5 mm). The secondary metabolite compounds of ethyl acetate extract were alkaloids, flavonoids and steroids. Bioactive compounds found in the Söfö-söfö ethyl acetate extract with potential antimicrobial activity were hexadecanoic acid, stigmasterol, neophytadiene, methyl ester, squalene and phytol.